Drying shrinkage and cracking resistance of concrete made with ternary cementitious components. (15th September 2017) - Hu, Xiang; Shi, Zhenguo; Shi, Caijun; Wu, Zemei; Tong, Baihui; Ou, Zhihua; de Schutter, Geert
Highlights: Compressive strength of concrete cured under drying shrinkage is investigated. Slag and fly ash show different influences on drying shrinkage of concrete. The cracking resistance of concrete is more controlled by total drying shrinkage. Factorial design method is applicable for mixture proportion design. Abstract: The compressive strength, free and restrained drying shrinkage and cracking resistance of concrete under drying condition were investigated for ternary cementitious systems containing Portland cement, slag and fly ash. The restrained shrinkage test (ring test) was carried out following ASTMC1581 . The results showed that the increased replacement level of slag or fly ash from 0 to 50% led to a gradual decrease in 28d compressive strength of concrete. The free drying shrinkage increased with the increase of slag content, but reduced with the fly ash content. The cracking resistance was well related to the free drying shrinkage of concrete, other factors such as strength also showed certain effects on cracking resistance of concrete. The cracking resistance of concrete was enhanced with the addition of fly ash while weakened with the slag replacement level up to 50%.